Chemometric Insights Into Grape Stems: Antioxidant Capacity, Phenolic Composition, and Mineral Profile - MITIĆ, Milan; STANKOV-JOVANOVIĆ, Vesna P.; MITIĆ, Jelena; NIKOLIĆ, Jelena; KARIOTI, Anastasia; LAZARI, Diamanto (Studia Universitatis Babeș-Bolyai Chemia, 2024)
The primary objective of this investigation was to assess the total polyphenolic content (TPC), identify and quantify individual polyphenols, and evaluate their radical scavenging activity (RSA), as well as determine the mineral composition in stem extracts from nine distinct Vitis vinifera varieties. The total phenolic content in grape stem extracts ranged from 34.87 to 76.95 mg gallic acid equivalents (GAE) per gram of dry weight (d.w.). These extracts exhibited significant free radical scavenging activity, ranging from 0.344 to 0.898 mmol Trolox equivalents (TE) per gram d.w. Stem extracts were predominantly characterized by flavan-3-ols, flavonols, and phenolic acids. Catechin and quercetin-3-glucuronide were identified as the most abundant components, with concentrations of up to 1.858 mg/g d.w. and 1.315 mg/g d.w., respectively. Potassium (K) emerged as the most abundant element in all samples, with content ranging from 7.297 mg/g d.w. to 16.695 mg/g d.w., followed by calcium (Ca), phosphorus (P), and magnesium (Mg).